2022
DOI: 10.1097/inf.0000000000003558
|View full text |Cite
|
Sign up to set email alerts
|

Extended Versus Standard Antibiotic Course Duration in Children <5 Years of Age Hospitalized With Community-acquired Pneumonia in High-risk Settings: Four-week Outcomes of a Multicenter, Double-blind, Parallel, Superiority Randomized Controlled Trial

Abstract: Background: High-level evidence is limited for antibiotic duration in children hospitalized with community-acquired pneumonia (CAP) from First Nations and other at-risk populations of chronic respiratory disorders. As part of a larger study, we determined whether an extended antibiotic course is superior to a standard course for achieving clinical cure at 4 weeks in children 3 months to ≤5 years old hospitalized with CAP. Methods: In our multinational (Australia, New Zealand, Malaysia), double-blind, superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In 2022, the findings from the first clinical trial evaluating the duration of therapy for children hospitalized with CAP were reported [39 ▪▪ ]. McCallum et al performed a double-blind RCT assigning hospitalized children from Australia, New Zealand, and Malaysia with uncomplicated, radiographically confirmed CAP to approximately 5–6 days of antibiotics vs. 13–14 days of antibiotics.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%
“…In 2022, the findings from the first clinical trial evaluating the duration of therapy for children hospitalized with CAP were reported [39 ▪▪ ]. McCallum et al performed a double-blind RCT assigning hospitalized children from Australia, New Zealand, and Malaysia with uncomplicated, radiographically confirmed CAP to approximately 5–6 days of antibiotics vs. 13–14 days of antibiotics.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%
“…Importantly, our findings and the other mentioned studies seem to be in line with new evidence about the safety of short therapy in pediatric infectious diseases, such as pneumonia [ 10 ]: a recent review considered four clinical trials [ 23 , 24 , 25 , 26 ] aimed at analyzing the optimal duration of antibiotic therapy in children affected by non-hospitalized pneumonia, the conclusions of which are the same and indicate that in uncomplicated forms 5 days of antibiotic therapy are sufficient in the eradication of the infection. A similar conclusion can be applied to hospitalized patients [ 27 ] from a large multicenter study conducted in 2022, which showed that, in uncomplicated pneumonia cases, a 13–14-day cycle (defined as extended) does not exceed a standard 5–6-day cycle in healing at one month (extended course: n = 127/163, 77.9%; standard course: n = 131/161, 81%). In conclusion, fixed antibiotic durations provide straightforward guidance but do not take into account children’s characteristics or treatment response; a possible approach would be to individualize antibiotic durations via biomarker-assisted guidance such as C-reactive protein or procalcitonin, although these are non-specific indexes for bacterial infections [ 28 ].…”
Section: Discussionmentioning
confidence: 80%
“…Their results showed that 82.8% of outpatient antibiotic prescriptions for children with CAP were written for a duration of 10 days, whereas only 10.5% were written for a shorter duration [ 15 ]. However, multiple randomized control trials supporting shorter durations have since been published [ 3 , 4 , 5 , 6 ]. Pernica and colleagues published the SAFER trial in 2021, which compared five- and ten-day courses of high-dose amoxicillin for pediatric patients diagnosed with CAP in the emergency department (ED) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above studies provide data supporting short antibiotic durations for pediatric CAP treatment, but their application for hospitalized children with CAP may be limited since they were primarily completed in an outpatient setting. Another randomized control trial performed by McCallum and colleagues aimed to determine whether an extended antibiotic course was superior to a standard course of antibiotics for children hospitalized with uncomplicated CAP [ 6 ]. Patients received one to three days of intravenous (IV) antibiotics followed by oral amoxicillin/clavulanate (80 mg/kg/day amoxicillin) for a total of 13 to 14 days (extended group) or 5 to 6 days (standard group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation